'The Good Officer': Francesc Vendrell's Conflict Resolution Work in Afghanistan and East Timor. Issue 3 (27th May 2022) - Loyn, David
Abstract: This is an introduction to the Asian Affairs Special Section with articles based on long interviews of Francesc Vendrell, the former UN and EU envoy to Afghanistan and East Timor.